(RE) produção de famílias “incapazes”: paradoxos à convivência familiar de crianças e adolescentes institucionalizados - Cardoso, Gracielle Feitosa de Loiola (2017)
The objective of this research was to know the experiences of access to services / public policies of families with children in an institutional reception situation and the repercussions for the return to the relationship with their children. It is a relational object that pulsates in lands that are very strongly intertwined between the Single Social Assistance System and the Justice System. To carry out this study presupposes a complex movement that shows a saturated web of historical, cultural, political, economic and social mediations. From this perspective, we chose the qualitative research, carried out with the support of the oral source, as a way of getting as close as possible to the reality and historical processes experienced and counted by the subjects participating in the research. The narrative of three women, Cristina, Nega and Margareth, whose stories intersect not only through the institutionalization of their children, but also through a daily life that is crossed by inequalities, violence and abandonment. In order to help in this process, the narratives of workers working in the Justice System and the Single Social Assistance System also came on the scene: two social workers and an lawyer working in CREAS, an social worker and an psychologist from the Municipal Reception Service, an social worker of the Reception Service for children up to 06 years old, and four tutorial advisers. The orality allows us to understand how subjects give meaning to reality, the possibility of "giving life" to what is set in procedural records, medical records, reports and PIAs, to know the lives and stories behind the persons held As negligent, incapable or dependent. Thus, allowing access to other contours and living beyond the inability to care for their children. It was tried to raise questions that contribute so that families with institutionalized children have access to a social protection citizen and, the destitution of the familiar power, can be more and more an exception